Productivity and Dissolved Oxygen Controls on the Southern Ocean Deep‐Sea Benthos During the Antarctic Cold Reversal. Issue 10 (19th October 2021) - Stewart, Joseph A.; Li, Tao; Spooner, Peter T.; Burke, Andrea; Chen, Tianyu; Roberts, Jenny; Rae, James W. B.; Peck, Victoria; Kender, Sev; Liu, Qian; Robinson, Laura F.
Abstract: The Antarctic Cold Reversal (ACR; 14.7 to 13 thousand years ago; ka) phase of the last deglaciation saw a pause in the rise of atmospheric CO2 and Antarctic temperature, that contrasted with warming in the North. A reexpansion of sea ice and a northward shift in the position of the westerly winds in the Southern Ocean are well‐documented, but the response of deep‐sea biota and the primary drivers of habitat viability remain unclear. Here, we present a new perspective on ecological changes in the deglacial Southern Ocean, including multifaunal benthic assemblage (foraminifera and cold‐water corals) and coral geochemical data (Ba/Ca and δ 11 B) from the Drake Passage. Our records show that, during the ACR, peak abundances of thick‐walled benthic foraminifera Uvigerina bifurcata and corals are observed at shallow depths in the sub‐Antarctic (∼300 m), while coral populations at greater depths and further south diminished. Our ecological and geochemical data indicate that habitat shifts were dictated by (a) a northward migration of food supply (primary production) into the sub‐Antarctic Zone and (b) poorly oxygenated seawater at depth during this Antarctic cooling interval. Key Points: Shallow sub‐Antarctic sites show Antarctic Cold Reversal peaks in thick‐walled benthic foraminifera and cold‐water coral abundance Corals were largely absent at deeper and more southerly sites during this interval Northward displacement of productivity and low oxygen bottom waters was key to these changes in benthic ecology at 14ka